Sculpting the Transcriptome During the Oocyte-to-Embryo Transition in Mouse - Svoboda, Petr; Franke, Vedran; Schultz, Richard M (Current topics in developmental biology, 2015)
In mouse, the oocyte-to-embryo transition entails converting a highly differentiated oocyte to totipotent blastomeres. This transition is driven by degradation of maternal mRNAs, which results in loss of oocyte identity, and reprogramming of gene expression during the course of zygotic gene activation, which occurs primarily during the two-cell stage and confers blastomere totipotency. Full-grown oocytes are transcriptionally quiescent and mRNAs are remarkably stable in oocytes due to the RNA-binding protein MSY2, which stabilizes mRNAs, and low activity of the 5' and 3' RNA degradation machinery. Oocyte maturation initiates a transition from mRNA stability to instability due to phosphorylation of MSY2, which makes mRNAs more susceptible to the RNA degradation machinery, and recruitment of dormant maternal mRNAs that encode for critical components of the 5' and 3' RNA degradation machinery. Small RNAs (miRNA, siRNA, and piRNA) play little, if any, role in mRNA degradation that occurs during maturation. Many mRNAs are totally degraded but a substantial fraction is only partially degraded, their degradation completed by the end of the two-cell stage. Genome activation initiates during the one-cell stage, is promiscuous, low level, and genome wide (and includes both inter- and intragenic regions) and produces transcripts that are inefficiently spliced and polyadenylated. The major wave of genome activation in two-cell embryos involves expression of thousands of new genes. This unique pattern of gene expression is the product of maternal mRNAs recruited during maturation that encode for transcription factors and chromatin remodelers, as well as dramatic changes in chromatin structure due to incorporation of histone variants and modified histones.
Keywords: RNA Stability; Animals; Oocytes; Genome; transkriptom; zvířata; Mice; Transcriptome; Embryo, Mammalian; genom; vývojová regulace genové exprese; embryo savčí; oocyty; Gene Expression Regulation, Developmental; stabilita RNA; myši